2014
DOI: 10.1007/s12035-014-8785-7
|View full text |Cite
|
Sign up to set email alerts
|

Mst3b Promotes Spinal Cord Neuronal Regeneration by Promoting Growth Cone Branching Out in Spinal Cord Injury Rats

Abstract: Spinal cord injury is a severe clinical problem, and research searching activity molecular that can promote spinal cord injury repairing is very prevalent. Mst3b can promote repair of damaged peripheral nerves and the optic nerve, but has been rarely reported in spinal cord injury research. Through detecting its expression in different periods of injured spinal cord, we found that the expression of Mst3b was significantly upregulated in injured spinal cord neurons. Increasing Mst3b expression using adenovirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…In the KEGG pathway, the MAPK and neurotrophin signaling pathways were the top two signaling pathways affected by the candidate tsRNA-mRNA axes. Previous studies (Zhang et al, 2015;Hodgetts and Harvey, 2017;Fu et al, 2018) have explored the relationships between these pathways and SCI, indicating that MAPK-related molecules regulate the neuronal survival, synaptic function, and neurotransmitter release, and elicit the plasticity and growth of axons within the central nervous system after SCI. Additionally, another report (Keefe et al, 2017) described that the neurotrophins, including NGF, BDNF, and NT-3, targeted specific populations of neurons via their effects on the populations of neurons within diverse spinal tracts.…”
Section: Discussionmentioning
confidence: 99%
“…In the KEGG pathway, the MAPK and neurotrophin signaling pathways were the top two signaling pathways affected by the candidate tsRNA-mRNA axes. Previous studies (Zhang et al, 2015;Hodgetts and Harvey, 2017;Fu et al, 2018) have explored the relationships between these pathways and SCI, indicating that MAPK-related molecules regulate the neuronal survival, synaptic function, and neurotransmitter release, and elicit the plasticity and growth of axons within the central nervous system after SCI. Additionally, another report (Keefe et al, 2017) described that the neurotrophins, including NGF, BDNF, and NT-3, targeted specific populations of neurons via their effects on the populations of neurons within diverse spinal tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these studies showed that inosine could stimulate neurite outgrowth independently of NGF, in an Mst3b-dependent manner [40]. Mst3b activity was shown subsequently to be required for both optic and radial nerve regeneration in vivo [51], and was shown to be increased by SCI in rats and to promote the regeneration of spinal cord neurons following injury [52]. In the latter study, Mst3b was shown to promote phosphorylation of B-Raf, MEK1 and ERK1/2 in PC-12 cells.…”
Section: Mechanisms Of Actionmentioning
confidence: 98%
“…SD rats were randomly divided into six groups: Sham (n = 8), SCI (n = 7), SCI + NC antagonist (n = 6), SCI + miR-155-5p antagonist(n = 8), SCI + NC agomir (n = 7), and SCI + miR-155-5p agomir group (n = 6). The surgical procedure was carried out as previously described [22,23]. Briefly, SD rats received intraperitoneal anesthesia with 1% pentobarbital (30 mg/kg) before spinal cord injury.…”
Section: Establishment Of the Sd Rat Model Of Scimentioning
confidence: 99%